1999
DOI: 10.1103/physreve.59.3196
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of an extended Fredrickson-Andersen model

Abstract: We describe an extension of the Fredrickson-Andersen model ͑or n-spin facilitated kinetic Ising model͒ which exhibits a transition similar to a glass transition. Our extension incorporates long-range effects. Exact or numerically accurate results are obtained only for one dimension, but most conclusions apply more generally. The model exhibits a discontinuous drop in the specific heat as it is cooled through the transition temperature. This leads to an excess internal energy and a residual entropy at zero temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A variation of the SFMs with added "mean-field" facilitation was introduced in [95]: spins can flip if either at least f of their neighbours are up, or if the overall concentration of up-spins in the system is greater than some threshold c th . If the model without the added facilitation is reducible, such as in the case of the 2,1-SFM, then the extended model has a sharp dynamical transition when the concentration of up-spins reaches c th ; for lower concentrations (i.e.…”
Section: Variations On Spin-facilitated Modelsmentioning
confidence: 99%
“…A variation of the SFMs with added "mean-field" facilitation was introduced in [95]: spins can flip if either at least f of their neighbours are up, or if the overall concentration of up-spins in the system is greater than some threshold c th . If the model without the added facilitation is reducible, such as in the case of the 2,1-SFM, then the extended model has a sharp dynamical transition when the concentration of up-spins reaches c th ; for lower concentrations (i.e.…”
Section: Variations On Spin-facilitated Modelsmentioning
confidence: 99%
“…Moreover, as shown in figure 1, we found that the steady-state values of f A , were appreciably less than those given by equation ( 4), especially as x approaches x c . This is not too surprising, since even for the usual FA model mean-field theory does not provide a very good approximation [14]. In contrast to the steady-state value of f A , the fluctuations δf A = |f A − f A | in f A were found to depend quite strongly on the lattice size, and to increase somewhat in magnitude as x approached x c , while their relative magnitude increases rapidly because of the decrease in f A .…”
Section: Resultsmentioning
confidence: 95%
“…The values of x c that we found were between 0.75 and 0.76 for the square lattices and between 1.38 and 1.40 for the cubic lattices, which are much less than those predicted by equation ( 3), as expected. In addition the steady-state values of f A were much less than those predicted by equation ( 2), which is also not surprising, since even for the usual FA model mean-field theory does not provide a good approximation [9].…”
Section: L577mentioning
confidence: 85%